Long divergent haplotypes introgressed from wild sheep are associated with distinct morphological and adaptive characteristics in domestic sheep - Hong Cheng; Zhuangbiao Zhang; Jiayue Wen; Johannes A. Lenstra; Rasmus Heller; Yudong Cai; Yingwei Guo; Ming Li; Ran Li; Wenrong Li; Sangang He; Jintao Wang; et al. (PLoS Genetics, 2023)
The worldwide sheep population comprises more than 1000 breeds. Together, these exhibit a considerable morphological diversity, which has not been extensively investigated at the molecular level. Here, we analyze whole-genome sequencing individuals of 1,098 domestic sheep from 154 breeds, and 69 wild sheep from seven Ovis species. On average, we detected 6.8%, 1.0% and 0.2% introgressed sequence in domestic sheep originating from Iranian mouflon, urial and argali, respectively, with rare introgressions from other wild species. Interestingly, several introgressed haplotypes contributed to the morphological differentiations across sheep breeds, such as a RXFP2 haplotype from Iranian mouflon conferring the spiral horn trait, a MSRB3 haplotype from argali strongly associated with ear morphology, and a VPS13B haplotype probably originating from urial and mouflon possibly associated with facial traits. Our results reveal that introgression events from wild Ovis species contributed to the high rate of morphological differentiation in sheep breeds, but also to individual variation within breeds. We propose that long divergent haplotypes are a ubiquitous source of phenotypic variation that allows adaptation to a variable environment, and that these remain intact in the receiving population probably due to reduced recombination. Author summary Introgression, introducing beneficial alleles from wild relatives, has been repeatedly proved to play important roles in adaptation to various environments during animal domestication and subsequent breeds formation. Several adaptive introgressions have been reported in domestic sheep, however, the systemic exploration is still lacking. Using a collection of more than 1000 individuals including 154 domestic breeds and seven wild relatives, we describe the genomic introgression spectrum across worldwide domestic sheep. Interestingly, we found several functional genes associated with morphological traits located in the introgressed regions. Besides, the frequency of highly divergent haplotypes in numerous introgressed regions are quite different among domestic breeds, indicating selection acted on these fragments. We speculated that the introgressed fragments contribute to the fast morphological differentiation of ~1,400 distinct domestic breeds. Deciphering the phenotypic variations in response to different introgressed haplotypes can reflect underlying breeding mechanisms. Overall, our work proves the important effect of introgression on sheep breeding, and shows how introgression, selection and recombination shape the genetic and phenotypic diversity.